Qualitative Research a practical guide for health and social care researchers and practitioners - Ayton, Darshini; Tsindos, Tess; Berkovic, Danielle (Open textbook library., 2024)
This guide is designed to support health and social care researchers and practitioners to integrate qualitative research into the evidence base of health and social care research. Qualitative research designs are diverse and each design has a different focus that will inform the approach undertaken and the results that are generated. The aim is to move beyond the “what” of qualitative research to the “how”, by (1) outlining key qualitative research designs for health and social care research – descriptive, phenomenology, action research, case study, ethnography, and grounded theory; (2) a decision tool of how to select the appropriate design based on a guiding prompting question, the research question and available resources, time and expertise; (3) an overview of mixed methods research and qualitative research in evaluation studies; (4) a practical guide to data collection and analysis; (5) providing examples of qualitative research to illustrate the scope and opportunities; and (6) tips on communicating qualitative research.